2021
DOI: 10.1167/jov.21.11.3
|View full text |Cite
|
Sign up to set email alerts
|

The response to background motion: Characteristics of a movement stabilization mechanism

Abstract: When making goal-directed movements toward a target, our hand deviates from its path in the direction of sudden background motion. We propose that this manual following response arises because ongoing movements are constantly guided toward the planned movement endpoint. Such guidance is needed to compensate for modest, unexpected self-motion. Our proposal is that the compensation for such self-motion does not involve a sophisticated analysis of the global optic flow. Instead, we propose that any motion in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…In line with other research (e.g., Brenner & Smeets, 2015 ; Crowe et al, 2021 ), we find evidence that the response is most sensitive to motion signals close to the endpoint of one’s action. This is in contrast to the conclusions drawn by Abekawa and Gomi ( 2010 ), who suggested that the response was not modulated by the location of the motion signal relative to the planned movement endpoint.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In line with other research (e.g., Brenner & Smeets, 2015 ; Crowe et al, 2021 ), we find evidence that the response is most sensitive to motion signals close to the endpoint of one’s action. This is in contrast to the conclusions drawn by Abekawa and Gomi ( 2010 ), who suggested that the response was not modulated by the location of the motion signal relative to the planned movement endpoint.…”
Section: Discussionsupporting
confidence: 92%
“…People continuously use visual information to adjust their movements in dynamic environments (Brenner & Smeets, 2018 ). For example, when reaching to a target item their movement is pulled in the direction of motion of the target (Brenner, Smeets, & De Lussanet, 1998 ; Brouwer, Middelburg, Smeets, & Brenner, 2003 ; de Lussanet, Smeets, & Brenner, 2001 ) but also by motion onset in the surrounding area of that item (e.g., Brenner & Smeets, 1997 ; Gomi et al, 2006 ; Saijo et al, 2005 ; Whitney et al, 2003 ; Zhang et al, 2018 , 2019 ), presumably to stabilize the ongoing movement (Crowe et al, 2021 ). Since the visual system organizes its input into perceptually coherent objects and surfaces, it makes sense that this response to motion onsets might consider whether the surface at the anticipated movement endpoint is moving, and if not, how close the moving surface is to that endpoint.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations